Graves' orbitopathy : a multidisciplinary approach questions and answers - Wiersinga, Wilmar M.; Kahaly, George J. (Karger, 2017)
Ten years ago, the first edition of Graves' Orbitopathy: A Multidisciplinary Approach was published. Since then, the book has become very popular and much has happened in the field to warrant a third edition. What has not changed is the successful and attractive question-and-answer format of the book. In the 3rd, revised and expanded edition, new chapters have been added on co-morbidity, local treatment modalities, novel immunosuppressive therapy, detailed protocols, and questions frequently asked by patients. All chapters of the previous edition have been thoroughly updated. Subjects covered then include the pathology of Graves' Orbitopathy (GO) and the controversial views on its pathogenesis; assessment of changes using reliable measuring techniques; medical management of GO including established and alternative treatment options; technical explanations and illustrations of various surgical procedures; and finally, the molecular, immunologic, and clinical aspects of this complex disorder. Additionally, ample consideration is given to the new 2016 ETA/EUGOGO guidelines on the management of GO.